A-type lamins involvement in transport and implications in cancer?. Issue 1 (31st December 2022) - Scott, Nicholas R.; Parekh, Sapun H.
ABSTRACT: Nuclear lamins and transport are intrinsically linked, but their relationship is yet to be fully unraveled. A multitude of complex, coupled interactions between lamins and nucleoporins (Nups), which mediate active transport into and out of the nucleus, combined with well documented dysregulation of lamins in many cancers, suggests that lamins and nuclear transport may play a pivotal role in carcinogenesis and the preservation of cancer. Changes of function related to lamin/Nup activity can principally lead to DNA damage, further increasing the genetic diversity within a tumor, which could lead to the reduction the effectiveness of antineoplastic treatments. This review discusses and synthesizes different connections of lamins to nuclear transport and offers a number of outlook questions, the answers to which could reveal a new perspective on the connection of lamins to molecular transport of cancer therapeutics, in addition to their established role in nuclear mechanics.